2004
DOI: 10.1080/09537100410001682814
|View full text |Cite
|
Sign up to set email alerts
|

Dextran 40 reducesin vitroplatelet aggregation in peripheral arterial disease

Abstract: Dextran 40 has been used to prevent post-operative thrombosis. However, its antithrombotic and antiplatelet effects in peripheral arterial disease (PAD) are poorly understood. We studied the in vitro effects of Dextran 40 on platelet function in control subjects and PAD patients using whole blood methods. Platelet function was assessed in 20 control subjects and 20 PAD patients. Spontaneous platelet aggregation (SPA) and agonist-induced platelet aggregation in response to increasing concentrations of Dextran 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…Dextrans also have a platelet inhibiting effect, which can be used in peripheral arterial surgery to counteract thrombosis [31]. In a recent review by Hartog et al [11], 17 in vitro studies clearly indicate that HES results in a weaker and smaller clot measured with thrombelastography.…”
Section: Discussionmentioning
confidence: 98%
“…Dextrans also have a platelet inhibiting effect, which can be used in peripheral arterial surgery to counteract thrombosis [31]. In a recent review by Hartog et al [11], 17 in vitro studies clearly indicate that HES results in a weaker and smaller clot measured with thrombelastography.…”
Section: Discussionmentioning
confidence: 98%
“…The polymer dextran has been shown to possess anti-thrombotic and anti-platelet function [24]. A few studies have previously reported on the ability of dextran to reduce agonist induced platelet aggregation [25,26]. Platelets absorb dextran, with resultant changes in electrophoretic mobility; suggesting that the inhibitory effect of dextran on platelet function might be due to some alteration of platelet membrane function [27].…”
Section: Discussionmentioning
confidence: 99%
“…Plant tissues and cell cultures [Su, 1995] have been exploited for the production of useful products derived from cell walls, such as wood, biomaterials, and biomedical materials [Murdoch et al, 2004;Robless et al, 2004]. These products and their cells have unique properties, including high elasticity with low density, low thermal conductivity, and high biomedical adaptability.…”
Section: Introductionmentioning
confidence: 99%